A comparison of the economic value for enteric methane emissions with other biological traits associated with dairy cows - Bell, Matthew J.; Pryce, Jennie; Wilson, Paul (American Research Journals, 2016)
This is the first study to derive the economic value of enteric methane produced by a ruminant animal. There is considerable interest globally in selecting for low methane-emitting ruminant livestock, as methane is a potent greenhouse gas. However, before enteric methane can be included in a genetic selection index for breeding, the economic value for enteric methane needs to be derived. An animal model including a partial budget was used to derive economic values for a range of production and fitness (health and fertility) traits typically used in genetic selection of dairy cows with the addition of enteric methane. This study found that enteric methane (kilograms/lactation) has an economic value of -£1.68 per kg increase in methane per lactation. The economic value for enteric methane was of similar magnitude to the traits of milk fat yield (£1.14 per unit change in milk fat) and mastitis (-£1.55 per % incidence). Based on the variation seen in the dairy cow population in the UK, genetic selection on enteric methane has potential to increase herd profit per cow and reduce emissions. Even if the economic and abatement gains associated with selecting low methane producing livestock are relatively small, reductions in enteric methane emissions appear possible if a reliable and repeatable measure becomes available for use on commercial farms.